Tentes et rails. Les « jeunes » du Sud tunisien entre chômage, attente et protestation - Stefano Pontiggia (Ateliers d'Anthropologie)
Redeyef in south-west Tunisia is a mining town born of phosphate exploitation. After the Structural Adjustment Plan was implemented in 1986, the region plunged into a serious economic crisis that led to the redundancy of three-quarters of the employees working for the Compagnie des phosphates de Gafsa, the main employer in the region. Deteriorating social conditions led the population to launch a mass-revolt in 2008. After the 2011 revolution, the persistence of the economic crisis drove many unemployed young people to protest against the government by blocking phosphate production, with the goal of getting a job in the Compagnie or in the public sector. The article tells some of their stories, and analyses the reasons that drove them to act as they did. It shows that many of these protestors were unmarried men who, because of their lack of employment, were not in a position to fulfil the conditions that would make them adults: building a house and establishing a family. Protests appears to be a specific form of job-searching, echoing a particular local management of discontent that aims to organise waiting.